The Effect of Finger Hold Relaxation Technique on Pain Intensity of Back Pain in Third Trimester Pregnant Women At The Klambu Health Center - Nurya Kumalasari; Nurul Kodiyah22@gmail.com; Rizki Sahara (The Shine Cahaya Dunia Kebidanan, 2024)
Background; Acute is a part of body mechanism for self defence from the experience of problem. Some treatment for acute is the use non pharmacological therapies are Finger Hold relaxation. Based on the 2020 Indonesian health data profile report, there were 5,256,483 pregnant women. Complications from back pain that are not treated immediately can cause difficulty walking and worsening mobility. In Klambu Village according to an initial survey in the pregnant women class of Klambu, as many 8 pregnant women experience discomfort in back pain. The purpose of the study was to provide obstetric care with a focus on finger hold relaxation technique interventions to reduce the intensity of back pain. Methodology; This research make use of quasi experimental two group pretest – post test group design. Population of this research is patient of pregnant thirt trimester with 30 respondents. Sampling technique used accidental sampling. Data analyze in this research was paired t-test.  Result; The outcome of this research is there impact of fingerhold relactation with p-value 0,000; and there impact benson relactation with p value 0.000; It shows that there is any effect of fingerhold relactation. For the paired t test fingerhold relactation t value 8.806 and benson relactation t value 6.123 Conclusion; there was impact of fingerhold relactation for acute intensity in the patient of pregnant women third trimester on backpain